Floristic survey of two Atlantic Forest fragments in the municipalities of Amargosa and Elísio Medrado, Bahia State, Brazil - Costa, Maria Auxiliadora de Andrade; Guedes, Maria Lenise Silva (SITIENTIBUS série Ciências Biológicas, 2010)
The Atlantic Forest, composed by diverse forest physiognomies, is placed in an area of about 600,000 km², equivalent to almost 7% of the Brazilian surface. These areas are currently very fragmented due to stockbreeding and agriculture intensification and because of real state expansion, etc. The goal of this study was to build a floristic survey concerning phanerogamic flora in two fragments of the Submontane Seasonal Semideciduous Forest, located in the Elísio Medrado (12°56’45"S, 39°31’19"W) and Amargosa (13°1’48"S, 39°36’18"W) Counties, in Bahia, Brazil. The field work was carried out from May 2005 to April 2006, with quarterly visits to collect the botanic material, which is deposited in the Alexandre Leal Costa Herbarium Collection (ALCB). One hundred sixty nine species were found in the inventories, distributed in 121 genera and 48 families. In fragment 1, the families showing greater species richness were Fabaceae (13 spp.), Sapindaceae (9), Euphorbiaceae (6), Rubiaceae (6) and Solanaceae (6); in fragment 2, the families Fabaceae (17 spp.), Myrtaceae (9), Asteraceae (5), Malvaceae (5) and Sapindaceae (5). Machaerium condensatum Kuhlm. & Hoehne, collected in this survey, is a species with few samplings in the state of Bahia. The Sørensen index (Sø= 0.21) revealed that the studied fragments showed low floristic similarity, which might be associated to edaphic conditions and to anthropic pressure in the region.